Three-dimensional atom probe characterization of alloy element partitioning in cementite during tempering of alloy steel. - Zhu, C; Xiong, X; Cerezo, A; Hardwicke, R; Krauss, G; Smith, G (2007)
Hardness measurements confirm that the martensitic microstructure of an alloy steel, AISI/SAE 4340, is significantly more resistant to softening, compared to the martensitic microstructure of a high-purity Fe-0.4% C alloy, at tempering temperatures, 300-400 degrees C, just above the temperatures where cementite replaces transition carbides in the martensitic matrix. Three-dimensional atom probe (3DAP) analyses of the 4340 steel show that Si rejection from the cementite is first detected after low-temperature tempering for times of 1 h. After 10-h tempering at 400 degrees C, Mn and Cr contents are increased, and Ni contents decreased, in cementite according to their carbide- and non-carbide-forming tendencies, respectively. The results are discussed with respect to the diffusivity of the substitutional alloying elements in the 4340 steel, and the effect that such diffusion-controlled redistribution would have on maintaining fine distributions of cementite that resist softening during tempering.